EFEKTIVITAS PELAKSANAAN PEMERIKSAAN DALAM RANGKA MENINGKATKAN PENERIMAAN NEGARA DARI SEKTOR PAJAK (STUDI KASUS DI KPP TULUNGAGUNG) - FLORENTIN LISTYANINGTYAS, ELLYA Florentin (Jurnal Akuntansi AKUNESA, 2012)
Calculation of effectiveness in terms of the settlement is calculated based on the issuance and realization of the Tax Inspection Warrant (SP3) is completed, the years 2009-2010 have the same level of effectiveness is the percentage of effective criteria 100%, whereas in 2011 had sufficient levels of effectiveness with a percentage of 75% less effectiveness. The result of the effectiveness of the settlement in terms of acceptance of the results of which are calculated based on the realization of targets and inspection provisions, which in 2009 had 110.03% effectiveness of the criteria is very effective. While the 2010 has the effectiveness of 104.35% which includes the criteria are very effective. While in 2011 has the effectiveness of 105.02% which includes the criteria are very effective. Because of the good cooperation between inspectors with the taxpayer, then they have the level of awareness and adherence to high pajakannya obligations. SP3 includes successful completion because of KPP Tulungagung SP3 can always finish within the allotted time is one year, although not resolved in 2011 but did not leave a lot of balance. Similarly, mean performance of the KPP Tulungagung already well because it can meet the set targets, KPP performance so far has been very professional, given the realization is not far from what was targeted. Keywords : tax and effectiveness